Thermally responsive thermoplastic polyester composite degradable bone cement and preparation method thereof
Patent Information
- Application Number
- CN202611374451.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该体系的实施例虽然提及骨水泥具有面团期,但未涉及材料稳定的可塑操作时间窗口,材料固化时间较快
1、本发明制备的热响应型热塑性聚酯复合可降解骨水泥具有一定的可塑形时间(3~8 min),混合后可形成时长充足、状态稳定的面团期,既可注射器微创注射,也能手工揉捏填充形状不规则、大块、多腔隙骨损伤,临床适用范围更广。
Smart Images

Figure CN122998463A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical materials technology, and in particular to a thermally responsive thermoplastic polyester composite biodegradable bone cement and its preparation method. Background Technology
[0002] Bone cement is a type of medical filling and bonding material widely used in orthopedics and dental restoration. It is mainly used for clinical treatments such as vertebral body shaping, joint prosthesis fixation, bone defect filling, and repair of complex bone defects.
[0003] Polymethyl methacrylate (PMMA) bone cement has become one of the most widely used bone cement materials in clinical practice due to its high mechanical strength, fast curing speed, and excellent handling properties. However, it still has certain limitations that affect its clinical application: because its polymer backbone is mainly composed of stable carbon-carbon bonds, it is difficult to undergo effective degradation in vivo. After implantation, it remains at the defect site for a long time and lacks the ability to gradually degrade and replace with the formation of new bone tissue, which can easily affect bone tissue reconstruction and may lead to complications such as aseptic loosening. In addition, PMMA bone cement has a high elastic modulus (1~2 GPa), which is significantly different from the mechanical properties of natural bone tissue. It is prone to stress shielding effect and increases the risk of secondary fractures in adjacent bone tissue. At the same time, it releases a large amount of polymerization heat during curing (peak temperature generally exceeds 65℃), which may cause thermal damage to surrounding bone and soft tissues, further limiting its application in scenarios requiring bone regeneration and repair.
[0004] Calcium phosphate and magnesium phosphate bone cement systems are important inorganic bone cement materials for clinical bone defect repair, possessing good biocompatibility, osteoconductivity, and biodegradability. However, they still have many inherent performance defects that limit their clinical application: These bone cements are mainly composed of stacked inorganic mineral crystals, resulting in loose crystal stacking, weak interfacial bonding strength, uneven pore distribution after curing, poor overall density, and poor structural stability. Under the continuous action of body fluid infiltration, local tissue micromovement, and physiological and mechanical loads, they are prone to fragmentation, disintegration, and detachment, making it difficult to maintain the complete support morphology of the defect area in the long term and failing to provide a stable scaffold environment for bone regeneration. Meanwhile, traditional unmodified systems exhibit poor controllability in degradation, with degradation rates generally exceeding the regeneration and reconstruction speed of natural bone tissue. This can easily lead to a mismatch between material degradation and new bone growth timing. Before the new bone tissue has completed ingrowth and achieved effective mechanical integration, the bone cement scaffold has already degraded and been lost prematurely, severely interfering with the orderly repair process of bone tissue. Furthermore, this type of bone cement has significant shortcomings in mechanical properties, with relatively weak bending resistance, impact resistance, and fatigue performance, resulting in limited mechanical load-bearing capacity. When subjected to physiological loads such as limb weight-bearing and daily activities, it is prone to mechanical failures such as cracking and collapse, significantly limiting its clinical application in high-load and complex bone regeneration and repair scenarios.
[0005] To overcome the shortcomings of traditional bone cement systems, several novel biodegradable bone cement materials have been proposed in recent years. CN116407689A discloses a two-phase cycloenone bone cement, which uses hydrophobic vinyl monomers for copolymerization, and inorganic nanomaterials are loaded onto the reducing agent in a redox system. The resulting material exhibits good osteogenic activity and mechanical properties, but its embodiments all involve injecting the material into the bone defect site using a syringe during the "toothpaste stage," and do not disclose that the material can form a dough-like stage that can be kneaded and shaped by hand, making it impossible to manually fill complex, large bone defects with irregular shapes. CN119607269A improves upon this by using hydrophilic vinyl monomers and dissolving the reducing agent in the liquid phase, while using inorganic ceramic powders such as calcium phosphate and magnesium phosphate as solid-phase fillers, thereby improving the material's cell affinity and bone integration ability, and using inorganic fillers to maintain the material's mechanical properties through subsequent hydration and curing. However, although the embodiments of this system mention that the bone cement has a dough-like stage, they do not involve the stable, malleable working time window of the material, and the material's curing time is relatively fast.
[0006] In summary, existing biodegradable bone cements still suffer from insufficient mechanical properties and limited in-situ molding capabilities, making it difficult to simultaneously meet clinical needs for both operability and early mechanical support. Therefore, developing a novel bone cement material with good mechanical properties, low exothermic in-situ rapid curing, dual operation modes of injection and manual dough molding, and a certain degree of biodegradability is of great significance for expanding the application of biodegradable bone cement in bone defect repair. Summary of the Invention
[0007] Therefore, to overcome the shortcomings of existing technologies, this invention proposes a heat-responsive thermoplastic polyester composite biodegradable bone cement, the raw materials of which include mixture A, mixture B, and solid phase C: The mixture A comprises cycloenone acetal monomers and an oxidant in a redox initiation system; the mixture B comprises hydrophilic vinyl monomers, a crosslinking agent, and a reducing agent in a redox initiation system; the solid phase C is a thermoplastic polyester polymer powder.
[0008] Further, the cycloenone acetal monomer is selected from 2-methylene-1,3-dioxane (MDO), 2 Methylene 4 Phenyl 1,3 Dioxane (MDPL), 5,6 benzo[a] 2 Methylene 1,3 Dioxane-7-heptane (BMDO), 4,7 dimethyl 2 Methylene 1,3 One or more of dioxane-1,3,6-trioxane-1,3,6-octane (MTC).
[0009] The oxidant is selected from one or more of benzoyl peroxide, tert-butyl hydroperoxide, ammonium persulfate, and hydrogen peroxide.
[0010] The hydrophilic vinyl monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, and poly(ethylene glycol) methacrylate.
[0011] The crosslinking agent is a monomer containing two or more vinyl units, selected from one or more of polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, diacrylamide polyethylene glycol, dimethacrylamide polyethylene glycol, dimethacrylate phosphate, and diacrylate phosphate.
[0012] The reducing agent is selected from one or more of N,N-dimethyl-p-toluidine, sodium metabisulfite, sodium bisulfite, and ferrous sulfate.
[0013] The thermoplastic polyester polymer powder is preferably polycaprolactone (PCL) powder.
[0014] The molecular weight of the polycaprolactone (PCL) is 10-80 kDa, preferably 30-50 kDa.
[0015] The polycaprolactone (PCL) powder has a particle size of 80–300 mesh, preferably 200–300 mesh.
[0016] The biodegradable bone cement can be injected or shaped during its plasticity period and then filled into the site of bone injury.
[0017] The filling is performed in any of the following procedures: total joint replacement, vertebroplasty, bone defect reconstruction, and treatment of infectious lesions.
[0018] The present invention also provides a method for preparing the above-mentioned biodegradable bone cement, comprising the following steps: (1) Dissolve the oxidant in a cycloenone acetal monomer to obtain mixture A; (2) Mix the hydrophilic vinyl monomer, crosslinking agent and reducing agent evenly to obtain mixture B; (3) Before use, mix the mixture A, mixture B and solid phase C to obtain mixture D, stir evenly, and cure at room temperature to obtain biodegradable bone cement.
[0019] Mixture A and Mixture B must be stored separately and mixed only just before use to avoid premature redox polymerization.
[0020] Furthermore, in order to improve the uniformity of powder mixing and stirring efficiency, and to improve the operability of the material preparation process, step (3) preferably involves mixing the mixture A with the solid phase C in advance to fully wet the solid phase C, and then adding the mixture B to obtain the mixture D. After that, manual shaping or injection operations can be performed, and the material is cured to obtain biodegradable bone cement.
[0021] The molar ratio of the oxidant to the cycloenone acetal monomer is 0.001~0.2:1, preferably 0.01~0.04:1.
[0022] The molar ratio of the hydrophilic vinyl monomer to the cycloenone acetal monomer is 0.01~10:1, preferably 0.5~3:1.
[0023] The molar ratio of the crosslinking agent to the cycloenone acetal monomer is 0.001 to 0.5:1, preferably 0.01 to 0.2:1.
[0024] The molar ratio of the reducing agent to the cycloenone acetal monomer is 0.001~0.2:1, preferably 0.01~0.04:1.
[0025] The ratio of the mass (g) of the solid phase C to the total volume (ml) of mixture A and mixture B is 0.2~1.3:1, preferably 0.6~1.0:1; wherein the total volume of mixture A and mixture B is calculated by: based on the amount of substance (n), relative molecular mass (M), and corresponding density (ρ) of each component in mixture A and mixture B in their pure state, according to the formula Calculate the volume of each component and sum them up.
[0026] The stirring in step (3) is done manually at 23±4℃, with a stirring speed of 2±0.5 times / second and a stirring time of 10~30s.
[0027] In this process, biodegradable bone cement is induced by a room temperature redox initiation system to undergo free radical ring-opening polymerization of cyclic monomers, introducing biodegradable ester bond structures into the polymer network. At the same time, the heat of reaction released during in-situ polymerization drives the softening or partial melting of low-melting-point thermoplastic polyester polymer powder, which participates in the formation of the composite material structure, thereby obtaining a composite bone cement structure composed of a biodegradable polymer matrix and thermoplastic polyester.
[0028] The present invention also provides a bone defect repair product, comprising the biodegradable bone cement described in the above technical solution or the biodegradable bone cement obtained by the preparation method described in the above technical solution.
[0029] Furthermore, the bone defect repair products include, but are not limited to, finished bone cement formulations, complete bone cement kits, and individually packaged bone cement raw material components.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The heat-responsive thermoplastic polyester composite biodegradable bone cement prepared by this invention has a certain plasticity time (3~8 min). After mixing, it can form a dough with sufficient time and stable state. It can be injected with a syringe for minimally invasive purposes or kneaded by hand to fill irregular, large, and multi-cavity bone injuries, thus having a wider range of clinical applications.
[0031] 2. The reaction process does not require high temperature to initiate, and the maximum exothermic temperature does not exceed 42℃. It causes less thermal damage to tissues and will not produce high-temperature burns to surrounding bone and soft tissues like PMMA bone cement, thus greatly improving the safety of use during surgery.
[0032] 3. By changing the molecular weight, particle size, and solid-liquid ratio of polyester, the compressive strength (≥70 MPa) and elastic modulus (100~500 MPa) of the material can be precisely adjusted, effectively reducing the mechanical difference with human cancellous bone, significantly reducing stress shielding caused by long-term implantation, and avoiding secondary fractures of adjacent bones.
[0033] 4. The bone cement prepared by this invention has good in vivo biodegradability. Relying on the composite system of cycloenone acetal degradable monomer and thermoplastic polyester, the material can undergo uniform and stable gradual degradation in vivo without sudden disintegration or local residual accumulation. Attached Figure Description
[0034] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0035] Figure 1 This is a cross-sectional scan of the bone cement material in Embodiment 2 of the present invention; Figure 2 This is a cross-sectional scan of the bone cement material in Comparative Example 2 of the present invention; Figure 3 This is a comparison chart of the compressive strength results of bone cement materials in Examples 1-4 and Comparative Examples 1-2 of the present invention; Figure 4 This is a comparison chart of the elastic modulus results of bone cement materials in Examples 1-4 and Comparative Examples 1-2 of the present invention; Figure 5This is a comparison chart showing the in vitro degradation rate of bone cement materials from Examples 1-4 and Comparative Examples 1-2 after immersion in PBS solution at 37°C for 90 days. Detailed Implementation
[0036] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0037] Example 1: Thermally responsive thermoplastic polyester composite biodegradable bone cement sample 1 The raw materials include mixture A, mixture B, and solid phase C: wherein, mixture A comprises 2-methylene-1,3-dioxane (MDO) and benzoyl peroxide; mixture B comprises hydroxyethyl methacrylate, polyethylene glycol dimethacrylate, and N,N-dimethyl-p-toluidine; and solid phase C is PCL powder with a molecular weight of 50 kDa and a particle size of 300 mesh.
[0038] The bone cement preparation process is as follows: (1) Benzoyl peroxide (0.24 g, 1 mmol) was dissolved in 2-methylene-1,3-dioxane (MDO) (5.7 g, 50 mmol) to obtain mixture A; (2) Hydroxyethyl methacrylate (6.5 g, 50 mmol), polyethylene glycol dimethacrylate (0.6 g, 3 mmol) and N,N-dimethyl-p-toluidine (0.13 g, 1 mmol) were mixed evenly to obtain mixture B; (3) Premix the mixture A with the solid phase C (12.7 g), then add the mixture B and stir until evenly mixed. Manually shape the bone cement in the dough stage into a specific mold.
[0039] Example 2: Two thermally responsive thermoplastic polyester composite biodegradable bone cement samples The raw materials include mixture A, mixture B, and solid phase C: wherein, mixture A comprises 4, 7 dimethyl 2-Methylene-1,3-dioxane-heptane (DMMDO) and benzoyl peroxide; the mixture B includes hydroxyethyl methacrylate, polyethylene glycol dimethacrylate and N,N-dimethyl-p-toluidine; the solid phase C is PCL powder with a molecular weight of 50 kDa and a particle size of 200 mesh.
[0040] The bone cement preparation process is as follows: (1) Dissolve benzoyl peroxide (0.24 g, 1 mmol) in 4,7 dimethyl 2-Methylene-1,3-dioxane (DMMDO) (7.1 g, 50 mmol) was used to obtain mixture A; (2) Hydroxyethyl methacrylate (6.5 g, 50 mmol), polyethylene glycol dimethacrylate (1.0 g, 5 mmol) and N,N-dimethyl-p-toluidine (0.13 g, 1 mmol) were mixed evenly to obtain mixture B; (3) Premix the mixture A with the solid phase C (14.4 g), then add the mixture B and stir until evenly mixed. Manually shape the bone cement in the dough stage into a specific mold.
[0041] Example 3: Three thermally responsive thermoplastic polyester composite biodegradable bone cement samples The raw materials include mixture A, mixture B, and solid phase C: wherein, mixture A comprises 5,6-benzo-2-methylene-1,3-dioxane (BMDO) and benzoyl peroxide; mixture B comprises dimethylaminoethyl acrylate, polyethylene glycol dimethacrylate, and N,N-dimethyl-p-toluidine; and solid phase C is PCL powder with a molecular weight of 30 kDa and a particle size of 200 mesh.
[0042] The bone cement preparation process is as follows: (1) Benzoyl peroxide (0.24 g, 1.62 mmol) was dissolved in 5,6-benzo-2-methylene-1,3-dioxane (BMDO) (14.6 g, 90 mmol) to obtain mixture A; (2) Mix dimethylaminoethyl acrylate (7.2 g, 50 mmol), polyethylene glycol dimethacrylate (0.40 g, 2 mmol) and N,N-dimethyl-p-toluidine (0.20 g, 1.44 mmol) evenly to obtain mixture B; (3) Premix the mixture A with the solid phase C (22.6 g), then add the mixture B and stir until evenly mixed. Manually shape the bone cement in the dough stage into a specific mold.
[0043] Example 4: Four thermally responsive thermoplastic polyester composite biodegradable bone cement samples The raw materials include mixture A, mixture B, and solid phase C: wherein, mixture A comprises 2 Methylene 4 Phenyl 1,3 Dioxane (MDPL) and benzoyl peroxide; the mixture B includes methacrylic acid (MMA), polyethylene glycol dimethacrylate and N,N-dimethyl-p-toluidine; the solid phase C is PCL powder with a molecular weight of 30 kDa and a particle size of 200 mesh.
[0044] The bone cement preparation process is as follows: (1) Dissolve benzoyl peroxide (0.31 g, 1.28 mmol) in 2 Methylene 4 Phenyl 1,3 Dioxane (MDPL) (12.9 g, 80 mmol) was used to obtain mixture A; (2) Mix methacrylic acid (8.6 g, 100 mmol), polyethylene glycol dimethacrylate (0.20 g, 1 mmol) and N,N-dimethyl-p-toluidine (0.17 g, 1.28 mmol) evenly to obtain mixture B; (3) Premix the mixture A with the solid phase C (21.3 g), then add the mixture B and stir until evenly mixed. Manually shape the bone cement in the dough stage into a specific mold.
[0045] Comparative Example 1: Commercially available bone cement OSTEOPAL® Commercially available bone cement OSTEOPAL® is prepared by uniformly mixing the solid and liquid phases according to the instructions, and then manually shaping the bone cement during the dough stage to fill it into the specified mold.
[0046] Comparative Example 2: Biodegradable bone cement without the addition of thermoplastic polyester polymer powder The raw materials include mixture A and mixture B: wherein, mixture A comprises 4, 7 dimethyl 2-Methylene-1,3-dioxane-heptane (DMMDO) and benzoyl peroxide; the mixture B comprises hydroxyethyl methacrylate, polyethylene glycol dimethacrylate and N,N-dimethyl-p-toluidine.
[0047] The bone cement preparation process is as follows: (1) Dissolve benzoyl peroxide (0.24 g, 1 mmol) in 4,7 dimethyl 2-Methylene-1,3-dioxane (DMMDO) (7.1 g, 50 mmol) was used to obtain mixture A; (2) Hydroxyethyl methacrylate (6.5 g, 50 mmol), polyethylene glycol dimethacrylate (1.0 g, 5 mmol) and N,N-dimethyl-p-toluidine (0.13 g, 1 mmol) were mixed evenly to obtain mixture B; (3) Mix liquid A and liquid B evenly, and manually shape the bone cement in the dough stage into a specific mold.
[0048] The test mainly includes the following aspects: 1. Morphological and structural testing of bone cement materials The bone cement samples from Example 2 and Comparative Example 2, after curing, were subjected to brittle fracture in a liquid nitrogen environment. The fracture surfaces were then vacuum-sprayed with gold, and the microstructure and component interface bonding of the materials were observed using field emission scanning electron microscopy (SEM). Figure 1 , Figure 2 The images shown are cross-sectional scans of Example 2 and Comparative Example 2, respectively.
[0049] The results showed that the cross-section of Example 2 had a continuous and dense structure, and the thermoplastic polyester particles were well bonded to the polymer matrix. Combined with the analysis of the material preparation process, it was shown that the thermoplastic polyester particles did not only exist as inert fillers, but participated in the formation of the internal composite structure of the material during the polymerization process.
[0050] 2. Tests on the maximum curing temperature and plastic working time of bone cement The method for testing the maximum curing temperature is as follows: After mixing all the bone cement materials of the examples and comparative examples evenly according to the corresponding operating methods, immediately pour them into the prefabricated mold and start timing. Use thermocouples to continuously measure the temperature and observe it in real time. Stop the test when the temperature begins to drop. According to the obtained temperature change curve over time, the peak value is the maximum curing temperature.
[0051] The method for testing the plasticity working time is as follows: All bone cement materials from the examples and comparative examples were mixed evenly according to their respective operating methods and then manually shaped. Timing began when the material formed a uniform, continuous, and kneadable dough-like state, and stopped when the material significantly hardened due to the curing reaction and could no longer be manually shaped. This time interval was defined as the plasticity working time of the material. The test results are shown in Table 1.
[0052] Table 1. Maximum curing temperature and working time of bone cement materials
[0053] The results showed that the biodegradable bone cement provided by this invention has a significantly lower maximum curing temperature compared to traditional PMMA bone cement (Comparative Example 1). Examples 1-4 all show minimal heat generation during curing, with the maximum curing temperature not exceeding 42°C, resulting in minimal thermal damage to tissues. In particular, Example 4 achieved a maximum temperature of 37.4°C, close to normal human body temperature, and the dough-like curing window time, allowing for manual shaping, also meets clinical requirements.
[0054] In Comparative Example 2, the bone cement system without PCL powder reached a maximum temperature of 121.4℃ during polymerization and curing, and no obvious dough-like plastic operation stage was observed. The PCL-containing composite bone cements prepared in Examples 1 to 4 all exhibited a certain dough-like plastic operation stage during curing, and their maximum curing temperature was also lower than that of Comparative Example 2. This indicates that the introduction of PCL can not only give bone cement a dough-like plastic operation stage and improve its clinical processability, but also significantly reduce the maximum polymerization and curing temperature and alleviate the defect of excessive exothermic curing.
[0055] 3. Mechanical property testing of bone cement The mechanical properties of bone cement were tested according to international standard ISO 5833-2002. All bone cement materials from the examples and comparative examples were mixed thoroughly according to their respective operating methods, air bubbles were removed, and the mixture was filled into cylindrical molds with a diameter of 5 mm and a height of 10 mm. After curing, the molds were removed. The upper and lower surfaces of all samples were polished to be parallel, and the prepared specimens were subjected to compression testing on a universal testing machine (LLOYD LD-5 model, 2.5 kN sensor). The loading speed was 1 mm / min, and the test was stopped when the maximum compressive strength reached its peak, the sample fractured, or the sensor value reached its limit. Three parallel samples were used in each group, and the average value was taken. The compressive strength and elastic modulus of the bone cement were calculated based on the stress-strain curve. The test results of the mechanical properties of bone cement are shown in Table 2, and the test data are plotted in […]. Figure 3 , Figure 4 .
[0056] Table 2 Test results of mechanical properties of bone cement materials
[0057] The results showed that although the compressive strength of the biodegradable bone cement provided by the present invention (Examples 1-4) was slightly lower than that of the traditional PMMA bone cement (Comparative Example 1), it was still above 70 MPa, which was higher than that of the pure polymer matrix material in Comparative Example 2. Furthermore, the elastic modulus of all examples was significantly lower than that of Comparative Example 1, falling within the mechanical range of cancellous bone (10-900 MPa), thus better matching the mechanical properties of bone tissue and reducing the likelihood of secondary fractures of the adjacent bone tissue at the implantation site.
[0058] 4. In vitro degradation test of bone cement All bone cement samples from the examples and comparative examples were cleaned with ethanol and water sequentially, dried, and weighed to determine their initial mass. The bone cement was then immersed in 3 mL of phosphate precipitate (PBS) solution and stored at 37°C for 90 days, with the PBS replaced every 7 days. After immersion, the samples were removed from the solution, dried overnight, and weighed again to determine their final mass. Three parallel samples were used for each group, and the average value was taken. The degradation rate was calculated using the following formula:
[0059] The test results are shown in Table 3. The degradation rate changes with time as follows: Figure 5 .
[0060] Table 3. In vitro degradation of bone cement materials
[0061] The results showed that the materials in Examples 1-4 all exhibited good degradation rates after 90 days under in vitro physiological conditions. The degradation of the material in Example 1 was the most significant, with a representative sample degradation rate of 23.1%. The good degradation rates of the materials in Examples 1-4 and Comparative Example 2 indicate that the ester groups introduced by the ring-opening polymerization of cycloalkenone acetal compounds provide better degradation performance for the materials. The degradation rate of the pure polymer matrix material in Comparative Example 2 was higher than that in Examples 1-4 because the introduced PCL degraded more slowly, which affected the degradation rate of the composite bone cement material to some extent. In contrast, the degradation rate of the representative sample of Comparative Example 1 was only 1.2% after 90 days, indicating poor degradation performance and a degradation rate much lower than that in Examples 1-4. This demonstrates that the biodegradable bone cement constructed in this invention has superior degradation performance compared to traditional PMMA bone cement.
[0062] The above descriptions of the embodiments are only for the purpose of helping to understand the technical solutions and core concepts of the present invention. For those skilled in the art, various modifications, improvements and alterations can be made to the present invention without departing from the principles of the present invention; the present invention is not limited to the embodiments shown herein, and the general technical principles described herein can be applied to other equivalent implementation methods. All modifications that do not depart from the spirit and substance of the present invention fall within the protection scope defined by the claims of the present invention.
Claims
1. A thermo-responsive thermoplastic polyester composite biodegradable bone cement, characterized in that, Its raw materials include mixture A, mixture B, and solid phase C: The mixture A comprises cycloenone acetal monomers and an oxidizing agent; the mixture B comprises hydrophilic vinyl monomers, a crosslinking agent, and a reducing agent; and the solid phase C is a thermoplastic polyester polymer powder.
2. The biodegradable bone cement according to claim 1, characterized in that, The cycloenone acetal monomer is selected from 2-methylene-1,3-dioxane (MDO), 2 Methylene 4 Phenyl 1,3 Dioxane (MDPL), 5,6 benzo[a] 2 Methylene 1,3 Dioxane-7-heptane (BMDO), 4,7 dimethyl 2 Methylene 1,3 One or more of dioxane-1,3,6-trioxane-1,3,6-octane (MTC); and / or, the oxidant is selected from one or more of benzoyl peroxide, tert-butyl hydroperoxide, ammonium persulfate, and hydrogen peroxide.
3. The biodegradable bone cement according to claim 1, characterized in that, The hydrophilic vinyl monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl methacrylate, dimethylaminoethyl methacrylate, and poly(ethylene glycol) methacrylate; and / or, the crosslinking agent is selected from one or more of polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, diacrylamide polyethylene glycol, dimethacrylamide polyethylene glycol, dimethacrylate phosphate, and diacrylate phosphate; and / or, the reducing agent is selected from N, N One or more of dimethyl-p-toluidine, sodium metabisulfite, sodium bisulfite, and ferrous sulfate.
4. The biodegradable bone cement according to claim 1, characterized in that, The thermoplastic polyester polymer powder is polycaprolactone (PCL) powder.
5. The biodegradable bone cement according to claim 4, characterized in that, The polycaprolactone (PCL) has a molecular weight of 10-80 kDa and a powder particle size of 80-300 mesh.
6. A method for preparing the biodegradable bone cement according to any one of claims 1 to 5, comprising the following steps: (1) Dissolve the oxidant in a cycloenone acetal monomer to obtain mixture A; (2) Mix the hydrophilic vinyl monomer, crosslinking agent and reducing agent evenly to obtain mixture B; (3) Before use, mix the mixture A, mixture B and solid phase C to obtain mixture D, stir evenly, and cure at room temperature to obtain biodegradable bone cement.
7. The preparation method according to claim 6, characterized in that, The molar ratio of the oxidant to the cycloalkenyl acetal monomer is 0.001~0.2:1; and / or, the molar ratio of the hydrophilic vinyl monomer to the cycloalkenyl acetal monomer is 0.01~10:1; and / or, the molar ratio of the crosslinking agent to the cycloalkenyl acetal monomer is 0.001~0.5:1; and / or, the molar ratio of the reducing agent to the cycloalkenyl acetal monomer is 0.001~0.2:
1.
8. The preparation method according to claim 6, characterized in that, The ratio of the mass (g) of the solid phase C to the total volume (ml) of the mixture A and the mixture B is 0.2~1.3:
1.
9. The preparation method according to claim 6, characterized in that, The stirring in step (3) is done manually at 23±4℃, with a stirring speed of 2±0.5 times / s and a stirring time of 10~30s.
10. A bone defect repair product, characterized in that, The biodegradable bone cement includes any one of claims 1 to 5 or any one of claims 6 to 9.
Citation Information
Patent Citations
Absorbable bioactive bone cement as well as preparation method and application thereof
CN116407689A
Low-shrinkage self-reinforced degradable bone cement as well as preparation method and application thereof
CN119607269A
